Durability of Portland Concrete Containing Polymeric Fillers and Fly Ash - Brostow, Witold; Chetuya, Nonso; Gençel, Osman; Hong, Hee Jae; Menard, Noah; Sayana, Susmitha; Gençel, Osman (Kaunas Univ Tech, 2020)
Portland concrete suffers in service brittle failure, extensive crack propagation, and wear rates increasing with time. In spite of all the effort expended, these problems persisted when we had started our project. We used several polymeric fillers and fly ash. Higher compressive moduli than the starting concrete are seen for some compositions, the highest for 5 % of one of the polymers + 5 % fly ash. The same composition has the lowest Taber abrasive wear loss. All composites show lower wear loss values than Portland concrete. After 25 days of acidic degradation in 4.0 molar aq. HCl, the starting Portland concrete suffers stronger degradation that our composites. Polymer swelling mitigates acidic degradation. Repetitive freeze-thaw cycles between 15oF and 85oF show disappearance of the deep voids present before the first cycle in our composites but not in the Portland cement. While the use of fly ash mitigates contamination of the environment, it is the combination of fly ash with polymers which provides significantly improved properties - tribological, chemical and mechanical ones - of the Portland concrete.
Keywords: Concrete Embrittlement; Concrete Modification; Concrete Tribology; Concrete Abrasion